Pengembangan Usaha Ekonomi Produktif dan Manajemen Usaha pada Kelompok Dasawisma Kelurahan Krobokan Semarang - Diah Ayu Kusumawati; Arizqi Arizqi; Devi Permatasari (Yumary: Jurnal Pengabdian kepada Masyarakat, 2022)
Purpose : This community service aims to develop productive economic businesses by utilizing the natural potential of the surrounding environment to open up business opportunities by empowering and re-activating the main tasks of the PKK, especially in the dasawisma group. Method : The implementation of this community service uses counseling and training methods for creative economy development and business management in the dasawisma group of Krobokan Village which is carried out offline and data collection through questionnaires.  Result :  The results of this community service show that counseling and training for the dasawisma group of Krobokan Village, both those who already have a business and housewives who are able to provide business management knowledge and develop creative economic businesses by utilizing the potential of the natural surroundings so that they are able to develop sustainable businesses.  Limitation : The application of good business management is very much needed in developing creative economy businesses for the Dasawisma group who want to start a business, so a simple and gradual method of delivering business management is needed to make it easier to implement.  Research Contribution : This training is expected to be a reference in the application of academic knowledge to the general public, especially in the field of management science